Adult to adult right lobe living donor liver transplantation: does biological relationship matter?. Issue 4 (January 2017) - Zhang, Wei; Tan, Yifei; Shen, Shu; Jiang, Li; Yan, Lunan; Yang, Jiayin; Li, Bo; Wen, Tianfu; Zeng, Yong; Wang, WenTao; Xu, Mingqing
Abstract : Abstract: The influence of the biological relationship between the donor and the recipient is rarely discussed in living donor liver transplantation (LDLT), although it is believed to be an important risk factor in other types of organ transplantations. A total of 272 consecutive patients undergoing adult to adult right lobe LDLT were retrospectively analyzed and stratified into a nonbiologically related (NBR) group (69 patients) and a biologically related (BR) group (203 patients). The preoperative data and postoperative outcomes of both recipients and donors were evaluated. More than two-thirds of the recipients had histories of HBV infection, and hepatocellular carcinoma (HCC) was the main reason for the patients undergoing LDLT in both groups. The percentage of female donors in the NBR group was more than the percentage in the BR group ( P  = 0.000). There were no differences between the groups in postoperative laboratory testing or daily immunosuppression dose, and the complication rates in both the recipient and donor surgeries showed no significant differences. For patients with benign diseases, the cumulative 1-, 3-, 5-, and 10-year survival rate were 92.9% in the 4 periods in the NBR group and 89.1%, 87.6%, 83.7%, and 83.7%, respectively, in BR group, while for the patients diagnosed as HCC, if patients exceeding the Milan criteria were involved, the 5-year survival rate was 41.2%, compared to 82% for patients within the Milan criteria, which was nearly the same as for those with the benign disease. In conclusion, our findings suggested that the biological relationship between the donor and the recipient in adult to adult LDLT was not associated with the short- and long-term outcomes of recipients diagnosed with benign liver diseases and early stage HCC. Moreover, the criteria for patients diagnosed with HCC to undergo LDLT should be restrictively selected.